Pattern of ocular trauma - Hossain, MM; Mohiuddin, AA; Akhanda, AH; Hossain, MI; Islam, MF; Akonjee, AR; Ali, M (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):377-380 The abstract of this article is available on the PubMed website